Determination of shear wave velocity from borehole database in the Osaka Basin, Japan - Pathak, Dinesh; Iwasaki, Yoshinori; Nakagawa, Koichi (Journal of Nepal Geological Society, 2000)
The shear wave velocity (Vs) provides important information on the properties of subsurface material that has significance in earthquake engineering and in the other works to be carried out in the major cities on alluvial basins. An empirical relationship has been obtained for the Vs with the N value (from standard penetration test) and depth for different geological facies of varying age using the database of 84 investigation boreholes in the Osaka Basin. The calculated and observed shear wave velocities are very close to each other. The obtained equation has been applied to calculate Vs (m/sec) and to draw shear wave velocity profiles across the major sections of the Osaka Basin.